Comparative evaluation of minimally invasive 'tibial tuberoplasty' surgical technique versus conventional open surgery for Schatzker II–III tibial plateau fractures: design of a multicentre, randomised, controlled and blinded trial (TUBERIMPACT study). Issue 8 (3rd September 2019) - Vendeuvre, Tanguy; Monlezun, Olivier; Brandet, Claire; Ingrand, Pierre; Durand-Zaleski, Isabelle; Gayet, Louis-Etienne; Germaneau, Arnaud; Khiami, Frederic; Roulaud, Manuel; Herpe, Guillaume; Rigoard, Philippe
Abstract : Introduction: Fractures of the tibial plateau are in constant progression. They affect an elderly population suffering from a number of comorbidities, but also a young population increasingly practicing high-risk sports. The conventional open surgical technique used for tibial plateau fractures has several pitfalls: bone and skin devascularisation, increased risks of infection and functional rehabilitation difficulties. Since 2011, Poitiers University Hospital is offering to its patients a new minimally invasive technique for the reduction and stabilisation of tibial plateau fractures, named 'tibial tuberoplasty'. This technique involves expansion of the tibial plateau through inflation using a kyphoplasty balloon, filling of the fracture cavity with cement and percutaneous screw fixation. We designed a study to evaluate the quality of fracture reduction offered by percutaneous tuberoplasty versus conventional open surgery for tibial plateau fracture and its impact on clinical outcome. Methods and analysis: This is a multicentre randomised controlled trial comparing two surgical techniques in the treatment of tibial plateau fractures. 140 patients with a Schatzker II or III tibial plateau fracture will be recruited in France. They will be randomised either in tibial tuberoplasty arm or in conventional surgery arm. The primary outcome is the postoperative radiological step-off reduction blindly measured on CT scan (within 48 hours post-op). Additional outcomes include other radiological endpoints, pain, functional abilities, quality of life assessment and health-economic endpoints. Outcomes assessment will be performed at baseline (before surgery), at day 0 (surgery), at 2, 21, 45 days, 3, 6, 12 and 24 months postsurgery. Ethics and dissemination: This study has been approved by the ethics committee Ile-De-France X and will be conducted in accordance with current Good Clinical Practice (GCP) guidelines, Declaration of Helsinki and standard operating procedures. The results will be disseminated through presentation at scientific conferences and publication in peer-reviewed journals. Trial registration number: Clinicaltrial.gov:NCT03444779 .